2022
DOI: 10.1155/2022/4285328
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Integrative Data Intelligence Model for Construction Cost Estimation

Abstract: Construction cost estimation is one of the essential processes in construction management. Project cost is a complex engineering problem due to various factors affecting the construction industry. Accurate cost estimation is important in construction management and significantly impacts project performance. Artificial intelligence (AI) models have been effectively implemented in construction management studies in recent years owing to their capability to deal with complex problems. In this research, extreme gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…The results are contrasted with what was shown by previous reviews, such as references [36,37,84], showing that there is a growing trend of research on the subject. This review provides the classification of the articles found by PMI knowledge areas (Project Management Institute 2017), finding that the greatest interest of the academic community is in cost management [53,58,64,74,79], quality management [12,73,77], time management [57,60,62,82], and, finally, scope management [11,81,87]. There is a knowledge gap in the use of emerging technologies (big data, data science, and artificial intelligence) in the areas of stakeholder management, communications, and human resources, at least in the construction and civil works sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are contrasted with what was shown by previous reviews, such as references [36,37,84], showing that there is a growing trend of research on the subject. This review provides the classification of the articles found by PMI knowledge areas (Project Management Institute 2017), finding that the greatest interest of the academic community is in cost management [53,58,64,74,79], quality management [12,73,77], time management [57,60,62,82], and, finally, scope management [11,81,87]. There is a knowledge gap in the use of emerging technologies (big data, data science, and artificial intelligence) in the areas of stakeholder management, communications, and human resources, at least in the construction and civil works sector.…”
Section: Discussionmentioning
confidence: 99%
“…Project cost management (22 records) mainly features the use of emerging technologies to perform budget forecasting and projection [77,79,85], as well as the early detection of anomalies in financial and operational data [8,53,58]. Data science is also used to simulate different scenarios and assess the impact of decisions on the final project budget [64,68,74].…”
Section: Question 2-what Are the Most-used Methodological Routes And ...mentioning
confidence: 99%
“…Construction cost estimation is a critical component of project management, as it influences decision-making, budget allocation, and project success (Zainab, H. A., Abbas, M. B., Murizah, K., & Zainab, A.K., 2022). Several challenges commonly impact the accuracy of cost estimation, including incomplete information, uncertainties, and changing requirements (Aftab, H. M., Ismail, A. R.,Mohd, R. A., Asmi, A. A.,, 2014).…”
Section: Challenges In Construction Cost Estimationmentioning
confidence: 99%
“…However, the ARIMA model is unsuitable for capturing the nonlinearities of time series in engineering costs [2], which negatively affects prediction accuracy. To solve this problem, the support vector machine (SVM) [3][4][5], backpropagation (BP) neural network [6][7][8], and other machine learning models have been applied to cost prediction. Although such methods can effectively handle nonlinear problems, the SVM has limitations regarding data correlation processing and slow processing speed, and the BP neural network can quickly lose time series data and fall into local minimal values.…”
Section: Introductionmentioning
confidence: 99%